Quantitative comparisons of pulmonary artery hemodynamics before and after Pulsta valve implantation in patients with Tetralogy of Fallot using computational fluid dynamics - Baek, Seung Min; Choi, Kieun; Lee, Sang Yun; Lim, Hong Gook; Kim, Gi Beom; Seo, Jongmin (Frontiers in Cardiovascular Medicine, 2025)
Background and objectivesThe evaluation of percutaneous pulmonary valve implantation (PPVI) performance has been predominantly confined to assessing changes in the right ventricular volume using magnetic resonance imaging (MRI). This study aimed to evaluate the hemodynamic changes in the pulmonary arteries following PPVI using computational fluid dynamics (CFD) in patients with Tetralogy of Fallot.MethodsWe conducted CFD analysis based on MRI scans performed before and after PPVI using Pulsta valve in nine patients who underwent PPVI between 2016 and 2021. Statistical analysis, including Wilcoxon rank-sum tests and multivariable linear regression, was performed to examine the associations between CFD data and non-CFD factors, as well as changes in these parameters after PPVI.ResultsBefore PPVI, forward and backward flow velocities in the right pulmonary artery (RPA) were higher than those in the left pulmonary artery (LPA) and main pulmonary artery (MPA) (forward: MPA/RPA/LPA = 19.9/32.7/19.3 cm/s, backward: MPA/RPA/LPA = 10.1/17.0/9.1 cm/s). After PPVI, velocities decreased (forward: MPA/RPA/LPA = 13.3/14.2/8.3 cm/s, backward: MPA/RPA/LPA = 2.3/2.6/1.7 cm/s), reducing the differences among PAs. After PPVI, the vorticity (RPA; 3.9–1.6/s, p = 0.008, LPA; 4.4–1.8/s, p = 0.011, MPA; 5.4–1.5/s, p = 0.008), and energy dissipation (104.1–38.1 mW, p = 0.028) decreased significantly, whereas changes in the Womersley and Reynolds numbers were not statistically significant. There was no correlation between the right ventricular end-diastolic volume index and energy dissipation, and the changes in each of them were also unrelated to each other.ConclusionA deeper understanding of the hemodynamics of pulmonary arteries using CFD can aid in evaluating the effectiveness of PPVI and refining its indications in patients with Tetralogy of Fallot.